RESEARCH STRATEGY FOR INCREASING HUMAN RESOURCES CONTRIBUTION THROUGH HUMAN RESOURCE SCORECARD DESIGN AT PT NASIO KARYA PRATAMA - Mohammad Fayruz (SEAN Institute, 2022)
The purpose of this study were to identify HR Deliverables (as objectives strategic, lagging and leading indicator, and aiming decision), alignment process beetwen HR Deliverables with human resource architechture, and finally making decision about enlarging human resources programs. This study too was assessment design scorecard with gap analysis and than used indicator index to assess there performance. The purpose to assessment is to know performance scorecard, especially lagging indicator this period. The result of these assessment to used make decision enlarge human resources programs for management.